Relationships Between Anxiety Symptoms, Hopelessness and Suicidal Ideation Among Parental Caregivers of Mandarin-Speaking Children With Speech Impairment: The Mediating Effect of Depressive Symptoms - Ma, Si-Wei; Lai, Sha; Yang, Yan-Yan; Zhou, Zhongliang; Yang, Bin-Ting; Zheng, Gu-Zheng-Yue; Gao, Jianmin; Lu, Li (Frontiers in Psychiatry, 2021)
Background Determining the mental health status of parents who chronically care for a child with speech impairment is important for developing appropriate interventions to improve both parents’ and children’s health and achieve a win-win situation. Unfortunately, no study in China has explored this issue. This study investigated the differences in four aspects of mental health between maternal and paternal caregivers for the Mandarin-speaking children with speech impairment and determine whether depressive symptoms mediate the relationships between anxiety symptoms and suicidal ideation, hopelessness and suicidal ideation. Methods This cross-sectional questionnaire survey was conducted in February 2020 by sending a link to the predesigned electronic questionnaire in WeChat. Standardized assessment tools were employed. Hierarchical multiple logistic regression was conducted to examine the associations between various factors and suicidal ideation, and two separate structural equation models were performed to evaluate the mediating effects of depressive symptoms in the relationship between anxiety symptoms and suicidal ideation as well as between hopelessness and suicidal ideation. Results This study included 446 parental caregivers of Mandarin-speaking children with speech impairment. Paternal caregivers had greater score than maternal caregivers on loss of motivation (one of the subdomains of hopelessness). Somatic complications of the child (OR=2.73, 95% CI: 1.09-6.67) and depressive symptoms (OR=3.38, 95% CI: 1.83-6.30) were positively associated with caregivers’ suicidal ideation. Having speech therapy of child (OR=0.54, 95% CI: 0.29-0.98) was negatively correlated with caregivers’ suicidal ideation. There was direct effect of depressive symptoms on suicidal ideation. Depressive symptoms play mediating roles on the relationships between anxiety symptoms (β=0.171, p<0.001) as well as between hopelessness and suicidal ideation (β=0.187, p<0.001). Conclusions Paternal and maternal caregivers of Mandarin-speaking children with speech impairment suffered from mental health problems. Preventive strategies and interventions to ameliorate parental psychological wellbeing, and health care policies to increase the accessibility to speech therapy care of children with speech impairment are imperative.